Immediate and Long-term Outcomes in High Anorectal Malformations in Males: A Prospective Observational Study - Pandya, Kashyap; Kacheriwala, Samir; Pandya, Ananyaa (Journal of Neonatal Surgery, 2025)
Background: High anorectal malformations (ARMs) represent a complex subset of congenital anomalies requiring staged surgical correction. While early survival has improved with advances in neonatal care, long-term functional outcomes such as fecal continence and urinary control remain critical markers of surgical success. Objectives: To evaluate immediate postoperative complications and long-term functional outcomes in male patients with high ARMs undergoing staged surgical management at a tertiary centre. Methods: This prospective observational study included 50 male neonates with high ARMs treated between January 2020 and January 2025 at SSGH, Vadodara. Patients underwent initial colostomy, posterior sagittal anorectoplasty (PSARP), and delayed colostomy closure. Outcomes assessed included stoma complications, continence status, constipation, urinary dysfunction, and mortality. Associations were analyzed using chi-square tests. Results: Stoma-related complications occurred in 48% of cases, while 34% experienced PSARP-related issues. At follow-up (2–5 years), 56% had good fecal continence, 28% experienced severe constipation, and 14% had urinary complications. No significant association was found between fistula type and continence (χ² = 6.798, p = 0.1469). The mortality rate was 12%. Conclusion: Staged PSARP remains an effective surgical strategy for high ARMs, with acceptable complication rates and encouraging long-term functional outcomes. However, constipation and urinary issues warrant continued multidisciplinary follow-up...